2019
DOI: 10.1002/asia.201901070
|View full text |Cite
|
Sign up to set email alerts
|

A Reduction‐responsive Amphiphilic Methotrexate‐Podophyllotoxin Conjugate for Targeted Chemotherapy

Abstract: Owing to the naturally high toxicity, poor water solubility,a nd other side effects of podophyllotoxin (PPT), its applicationsare limited.T oaddress theseissues, we developed an ew PPT delivery system, in which the hydrophilic drug methotrexate (MTX) and the hydrophobic drug PPT were linked by ar eduction-responsive disulfide bond to form an amphiphilic drug-drugc onjugatep rodrug (MTX-SS-PPT). The conjugate could self-assemble into spherical nanoaggregates in aqueous solution ands elf-deliver to tumor tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…To overcome these disadvantages, Hou and co-workers conjugated hydrophobic PPT and hydrophilic methotrexate (MTX) via a reduction-responsive disulfide bond. The nanoprodrug formulated by this amphiphilic drug conjugates the successfully improved tumor delivery of PPT [ 98 ]. Huang and co-workers synthesized an amphiphilic drug–drug conjugate from the hydrophilic anticancer drug irinotecan (Ir) and hydrophobic anticancer drug chloramphenicol (Cb) through hydrolyzable ester ligation.…”
Section: Categories Of Drug Conjugatesmentioning
confidence: 99%
“…To overcome these disadvantages, Hou and co-workers conjugated hydrophobic PPT and hydrophilic methotrexate (MTX) via a reduction-responsive disulfide bond. The nanoprodrug formulated by this amphiphilic drug conjugates the successfully improved tumor delivery of PPT [ 98 ]. Huang and co-workers synthesized an amphiphilic drug–drug conjugate from the hydrophilic anticancer drug irinotecan (Ir) and hydrophobic anticancer drug chloramphenicol (Cb) through hydrolyzable ester ligation.…”
Section: Categories Of Drug Conjugatesmentioning
confidence: 99%
“…In addition, MTX was able to target folic acid overexpressing tumor cells. The results indicated that the nano-formulation could significantly enhance the biocompatibility and decrease the toxicity of PPT [22] . Thus, it should be simple, effective and promising strategy to construct the carrier-free DDSs based on ADDC for synergistic cancer therapy.…”
Section: Introductionmentioning
confidence: 95%
“…Aiming at these problems, a lot of research has been done to develop carrier-free drug self-delivery systems based on amphiphilic drug-drug conjugate (ADDC) [18] , [19] , [20] . ADDC is an amphiphilic molecule formed by connecting hydrophilic drugs and hydrophobic drugs through chemical bonds, which can self-assemble into nano-drugs by hydrophobic forces to realize drug self-delivery [21 , 22] . These carrier-free DDSs possess well-defined structures, precise drug ratios, high drug loading capacity and low-toxicity metabolic pathways [3 , 23 , 24] .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is a proved fact that high dose of this antimetabolite involves parallel reactions in the human body leading to severe side effects like gastritis, nausea, hair loss, and abnormal liver function; hence these types of drugs required specific dosage based on the individual patient conditions and requires the administration of co-drugs like folic acid and folinic acid to avoid the side effects of methotrexate. [2][3][4][5] Another top marketed drug lenalidomide for the treatment of cancer is known to induce severe side effects like lowering the blood count, blood clot, and severe nerve damage. A. Toma et al have reported that continuous administration of lenalidomide may cause eosinophilic pneumonia due to adverse drug reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Methotrexate (amethopterin) most popular and universally used drug to treat cancer, generally a high dosage of methotrexate with leucovorin is used to treat cancer. However, it is a proved fact that high dose of this antimetabolite involves parallel reactions in the human body leading to severe side effects like gastritis, nausea, hair loss, and abnormal liver function; hence these types of drugs required specific dosage based on the individual patient conditions and requires the administration of co‐drugs like folic acid and folinic acid to avoid the side effects of methotrexate [2–5] . Another top marketed drug lenalidomide for the treatment of cancer is known to induce severe side effects like lowering the blood count, blood clot, and severe nerve damage.…”
Section: Introductionmentioning
confidence: 99%